Surface waves on the inhomogeneous interface between radiative electron–ion plasma and vacuum. (5th August 2021) - Maryam, N.; Rozina, Ch.; Arooj, B.; Asma, A.; Kourakis, I.
Abstract : The impact of temperature inhomogeneity, surface charge and surface mass densities on the stability analysis of charged surface waves at the interface between dense, incompressible, radiative, self-gravitating magnetized electron–ion plasma and vacuum is investigated. For such an incompressible plasma system, the temperature inhomogeneity is governed by an energy balance equation. Adopting the one-fluid magnetohydrodynamic (MHD) approximation, a general dispersion relation is obtained for capillary surface waves, which takes into account gravitational, radiative and magnetic field effects. The dispersion relation is analysed to obtain the conditions under which the plasma–vacuum interface may become unstable. In the absence of electromagnetic (EM) pressure, astrophysical objects undergo gravitational collapse through Jeans surface oscillations in contrast to the usual central contraction of massive objects due to enhanced gravity. EM radiation does not affect the dispersion relation much, but actually tends to stabilize the Jeans surface instability. In certain particular cases, pure gravitational radiation may propagate on the plasma vacuum interface. The growth rate of radiative dissipative instability is obtained in terms of the wavevector. Our theoretical model of the Jeans surface instability is applicable in astrophysical environments and also in laboratory plasmas.